2015
DOI: 10.1371/journal.pone.0136732
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Actin and Lipid Binding Sites in Ysc84 Are Required during Early Stages of Yeast Endocytosis

Abstract: During endocytosis in S. cerevisiae, actin polymerization is proposed to provide the driving force for invagination against the effects of turgor pressure. In previous studies, Ysc84 was demonstrated to bind actin through a conserved N-terminal domain. However, full length Ysc84 could only bind actin when its C-terminal SH3 domain also bound to the yeast WASP homologue Las17. Live cell-imaging has revealed that Ysc84 localizes to endocytic sites after Las17/WASP but before other known actin binding proteins, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Coupled with the direct interaction between actin and dynamin, actin polymerization at the site of the invagination then either could directly drive scission or could be associated with subsequent movement of the released vesicle within the cytoplasm ( 24 , 29 ). We have recently demonstrated that overexpression of an early endocytic protein, Ysc84, that binds Las17 at a site overlapping Rvs167 can cause retractions in endocytosis similar to the rvs167 deletion, supporting the in vivo importance of the Rvs167-Las17 interaction ( 55 ).…”
Section: Discussionmentioning
confidence: 77%
“…Coupled with the direct interaction between actin and dynamin, actin polymerization at the site of the invagination then either could directly drive scission or could be associated with subsequent movement of the released vesicle within the cytoplasm ( 24 , 29 ). We have recently demonstrated that overexpression of an early endocytic protein, Ysc84, that binds Las17 at a site overlapping Rvs167 can cause retractions in endocytosis similar to the rvs167 deletion, supporting the in vivo importance of the Rvs167-Las17 interaction ( 55 ).…”
Section: Discussionmentioning
confidence: 77%
“…Ysc84 has been shown to regulate early steps of endocytosis 33 , and SH3YL1 is localized at dorsal ruffles, actin-rich membrane regions with intense receptor endocytosis 34 . Both proteins appear to contribute to the integration of F-actin and membrane morphology 44 . Accordingly, their SYLF domains have been shown to bind to phospholipids 34 , 44 , and in case of Ysc84 to actin 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Both proteins appear to contribute to the integration of F-actin and membrane morphology 44 . Accordingly, their SYLF domains have been shown to bind to phospholipids 34 , 44 , and in case of Ysc84 to actin 33 . Biochemically, CFS1 shows similarities to the behavior of Ysc84.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations